Analisis Kepuasaan Pelanggan Labbaik Chicken Menggunakan CSI (Customer Satisfaction Indek) - Resti Apipah; Khoirunnida; Syamsul Hidayat (Universitas Sains dan Teknologi Komputer, 2024)
This research aims to determine the level of customer satisfaction with the products and services provided by the Labbaik Chicken Company. The method used was a survey using an instrument in the form of a questionnaire which was delivered to a research sample of 330 respondents. Data was analyzed using the Customer Satisfaction Index (CSI) to measure the overall level of customer satisfaction. The research results showed that the CSI value obtained was 54.19 which was in the